Analisis kesilapan penggunaan perkataan sinonim bahasa Thai dalam kalangan pelajar Universiti Putra Malaysia - Mohamed Razak, Mohamed Ramdhan; Che Su, Norizan; Mustapha, Nik Farhan (Persatuan Linguistik Malaysia, 2014)
Synonyms are synonymous words with similar meanings. The use of synonymous words can be distinguished through the use of different sentence context. Even though synonymous words can be easily understood however most students are not able to distinguish the use of them correctly. Therefore, this study was undertaken to determine the aspects of the use of synonymous words in the Thai language as a foreign language among students at University Putra. The objective of this study was to identify the use of synonymous words in the Thai language used by students in appropriate sentence structure, and also identify the source of errors and word usage errors. To achieve the objectives of this research, the researcher used Contrastive analysis and Error analysis approaches. The sample for this study consisted of five level three students currently learning the Thai language at Universiti Putra Malaysia.